OCENA POTENCJAŁU PROJEKTU TYPU „KURS INTENSYWNY” JAKO NARZĘDZIA ROZWIJAJĄCEGO KOMPETENCJĘ INTERKULTUROWĄ EUROPEJSKICH NAUCZYCIELI JĘZYKA ANGIELSKIEGO - Strugielska, Ariadna; Strzemeski, Krzysztof (Neofilolog, 2019)
The intensive programme for the Development of Intercultural Competence of European Teachers of English (DICETE) aimed at the creation of an innovative module of intercultural teacher training for English as a lingua franca, which is being implemented in four partner universities as a part of the regular curriculum. This article presents how the concept of intercultural competence (IC) was negotiated by the participants and how it related to the particular stages of the project. Techniques in the programme for developing IC are described and the addresses to their repository in which they are available are given.